Occupational Stress Among Dental Professionals: A Bibliometric Analysis (2015-2024) - Dagli , Namrata; Haque, Mainul (Bangladesh Journal of Medical Science, 2025)
Occupational stress is a significant concern in the healthcare sector, particularly among dental professionals, who face unique stressors in their daily practice. This bibliometric analysis aims to provide an overview of the global research landscape on occupational stress among dental professionals. The study’s main objectives are to assess publication trends, citation trends, most impactful articles, most impactful sources, and most frequent themes of the studies on this topic. A systematic online search was conducted in the Dimensions database to gather relevant publications using keywords related to the topic. VOSviewer was used to visualize citation networks of articles, journals, and countries. Biblioshiny was used to identify the most frequently studied themes, most impactful publications, and citation trends. Our analysis revealed a significant increase in research output on occupational stress among dental professionals in recent years. However, the total number of articles is less. The highest number of citations was observed in 2018. The citation pattern of countries indicates that regions with advanced healthcare infrastructure and robust academic environments are more likely to generate research with a more considerable impact. The British Dental Journal is a highly cited journal that publishes on this topic. Key themes that emerged included job satisfaction, workload, burnout, musculoskeletal disorders, mental health, and COVID-19, suggesting a strong focus on stress’s impact on physical and psychological health, particularly during the pandemic. Factorial analysis reveals three main research themes: physical health risks, psychological well-being, and the effects of COVID-19. Additionally, it highlighted geographical differences, with different regions focusing on varied themes. This bibliometric analysis indicates a need for more longitudinal intervention-based research, particularly on preventive strategies and stress management programs tailored for dental professionals. BJMS, Vol. 24 No. 03 July’25 Page : 731-745